A case of acrogeria. - Miteva, L. (European Journal of Pediatric Dermatology, 2010)
A new case with the typical features of acrogeria in a 13-year-old girl is reported. The patient has always been noted to be small and thin with a marked loss of subcutaneous fat on the face and the distal extremities. The skin on her arms and legs has always been atrophic and fragile, causing an "atrophic appearance". There were large scars on both knees, but ulceration of the limbs never occurred. The patient had a remarkable face with a thin pinched nose and prominent eyes. The characteristic findings of patients with acrogeria and the nosologic place of this rarely reported premature aging syndrome are discussed.